2019
DOI: 10.1002/polb.24890
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the double melting peaks of poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) with a high HV content as revealed by in situ synchrotron WAXD/SAXS analyses

Abstract: We here reported the dual melting behaviors with a large temperature difference more than 50 °C without discernible recrystallization endothermic peak in isomorphous poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (P(HB‐co‐HV)) with a high HV content of 36.2 mol %, and the structure evolution upon heating was monitored by in situ synchrotron wide‐angle X‐ray diffraction/small‐angle X‐ray scattering (WAXD/SAXS) to unveil the essence of such double endothermic phenomena. It illustrated that the thinner lamellae wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The results of the structural and morphological analysis of the films are presented in Figure 4 . It is known that PHB crystallizes in an orthorhombic-like structure [ 46 ] belonging to the P212121 space group [ 47 ]. In the XRD patterns shown in Figure 4 a, some of the main reflections associated with the PHB polymer matrix can be found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the structural and morphological analysis of the films are presented in Figure 4 . It is known that PHB crystallizes in an orthorhombic-like structure [ 46 ] belonging to the P212121 space group [ 47 ]. In the XRD patterns shown in Figure 4 a, some of the main reflections associated with the PHB polymer matrix can be found.…”
Section: Resultsmentioning
confidence: 99%
“…Explicitly, all spectra display similar patterns, with reflections centered around 2θ angles of 13.95°, 16.84°, 20.5°, 22.7°, 25.9°, 27.7°, and 30.9°, which are due to the crystallographic planes (020), (110), (101), (111), (121), (040), and (002), respectively. Previous works have shown that these planes typically occur for the ordered orthorhombic structure of poly-β-hydroxybutyrate [ 46 , 48 , 49 ]. The patterns also exhibit a large halo positioned in the range of 35°–40°, which was also observed previously by D’Amico et al [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peak corresponding to the (110) plane shifted as a result of the thermal expansion of the crystal lattice. 45,46 The diffraction peaks associated with the (020) and (110) planes were observed up to 160 °C, meaning that they were also present at 130−150 °C, i.e., the temperature at which the melt-spinning was performed in this study. Therefore, the fact that melt-spinning is possible at temperatures lower than 170 °C in this work indicates that the amorphous portion is melt-flowed with the crystalline part, although some crystals remain.…”
Section: In Situ Waxd Experiments With Dscmentioning
confidence: 93%
“…For instance, PHB forms a compound with poly(3-hydroxyvalerate) (PHV) and, indeed, PHB-PHV copolymers show a lower melting temperature and crystallinity level [ 16 ]. Zhu et al also studied the melting behavior of a poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) having 36.2 mol% of hydroxyvalerate (HV) units by in situ synchrotron X-ray analyses [ 17 ]. The authors concluded that the low-temperature peak is due to melting of the thinner crystals with lower density because of the HV inclusion in the orthorhombic PHB cells, whereas the high-temperature peak is due to the fusion of the thicker PHB crystals with a small cell excluding HV units, which are confined in the amorphous phase.…”
Section: Theoretical Backgroundmentioning
confidence: 99%